Pengaruh DPK, CAR, BOPO, dan NPF terhadap Likuiditas pada Bank Umum Syariah - Intan Kania Rufaidah; Tjetjep Djuwarsa; Dimas Sumitra Danisworo (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to determine the effect of DPK, CAR, NPF, ROA for the liquidity of Islamic banks ini Indonesia during 2015 -2019, either simultaneously or partially. The object of this research is Islamic Commercial Banks in Indonesia. The research method used in this study is a correlational method with a quantitative approach. The data used is secondary data in the form of annual financial reports published by Bank Indonesia and OJK. The analytical method used is panel data regression using the analysis Eviews tool. The results of this study indicate that partially CAR, NPF, BOPO affect FDR. Meanwhile, DPK has no effect on FDR. The coefficient of determination (adjusted R2) of 0,3096 or 30,96%, which means that four independent variables can explain the dependent variable, while the rest influenced by other factors beyond the variables.